Inward- and Outward-Looking Rationales behind Kadi II. Issue 4 (December 2014) - Wimmer, Michael
The Kadi-'saga' has been a prime opportunity for the Court of Justice of the European Union (CJEU) to reaffirm both the constitutional foundations of the European Union and the relationship towards the United Nations legal order in the area of EU restrictive measures. There is a continuity between the rationale of the CJEU's first and second Kadi-judgments. The latter reveals a subtle interaction between internal and external driving forces. The major innovation is the formulation of a common law of EU sanctions. This framework balances EU constitutional standards with the preservation of the effectiveness of restrictive measures as a policy tool. Still, some fundamental rights gaps remain. From an external perspective, the judgment reflects some degree of openness, but does not provide a proper interface between international law and EU law, due to the asymmetric relations between the EU and the UN legal orders.